Evaluation of the influence of ultrasound and supercritical fluids in processes of polyphenolic compounds extraction from agroindustrial wastes (2017)
This work demonstrates the potential for obtaining polyphenolic compounds through the use of unconventional technologies: ultrasound assisted extraction and supercritical fluids extraction. The raw material employed in to develop the present work were spent coffee grounds, coffee cut-stems and naranjilla peel. Where these residues are produced in larg amount in Colombia. In addition, other raw materials from fruit and olive residues were analyzed. For this experimental stage, the physical-chemical characterization of the raw materials was initially carried out. Subsequently, the extraction conditions of chlorogenic acid was theoretically evaluated, in order to determine the best operating conditions. Then, extractions of the compounds of interest were carried out with technologies such as solvent extraction, Soxhlet extraction, ultrasonic assisted extraction and supercritical fluids extraction. This last was realized using CO2 as supercritical fluid. From this, it was determined the influence of each of these technologies in the polyphenolic compounds extraction. As a results were obtained compounds such as chlorogenic acid, ferulic acid, quercetin, vanillin, among others. In addition, these raw materials were used in integrated processes, through the development of different biorefineries. In these analysis were obtained of value-added products such as antioxidants, ethanol, xylitol, furfural and energy generation. Where, the economical, energetic and environmental aspects were evaluated (Texto tomado de la fuente)